Biomimetic biodegradable Ag@Au nanoparticle-embedded ureteral stent with a constantly renewable contact-killing antimicrobial surface and antibiofilm and extraction-free properties. (15th September 2020) - Gao, Liheng; Wang, Yiwei; Li, Yimeng; Xu, Mingxi; Sun, Gang; Zou, Ting; Wang, Fujun; Xu, Sijun; Da, Jun; Wang, Lu
Abstract: Urinary tract infections (UTIs) caused by the contamination of the ureteral stent and the pain associated with secondary stent extractions are worldwide problems in the treatment of urinary tract disorders. Here, we reported a biodegradable, long-term antibacterial, and extraction-free ureteral stent with a constantly renewable contact-killing surface and an antibiofilm function achieved by constructing a hyperbranched poly(amide-amine)-capped Ag shell and Au core nanoparticle (Ag@Au NP)-embedded fiber membrane-structured poly(glycolic acid)/poly(lactic-co-glycolic acid) (PGA/PGLA) ureteral stent. The ureteral stent showed fast contact-killing properties, i.e., 5 min for Escherichia coli and 10 min for Staphylococcus aureus, with an inhibition rate higher than 99%. In addition, gradient degradation of PGA/PGLA endowed the stent with a self-cleaning property and long-term antibacterial function by continuous exfoliation of the stent surface, thereby exposing the inner Ag@Au NPs and eliminating adherent bacteria and proteins. Subsequently, in the 16-day in vitro degradation test, the stent showed durable bactericidal activity, less total release of Ag and Au elements (6.7%, 8 μg), and low cytotoxicity (with a relative growth rate of >80% of L929 cells). In vivo experiments on a farm pig model showed that the stent exhibited a remarkable antibiofilm property and reduced the level of inflammatory and necrotic cells. After seven days of implantation, the stent showed a gradient degradation behavior and maintained structural integrity without the presence of any large fragments in the urinary system according to the B-ultrasonic examination. The as-developed biodegradable and renewable contact-killing antibacterial strategy was efficient in preparing the ureteral stent with antibiofilm and extraction-free properties to treat stent-induced UTI. Statement of significance This study presents a customized antibiofilm solution for biodegradable implants. Two particularly important aspects of this work are as follows: (1) The ureteral stent showed functions of bacterial inactivation and removal of dead bacterial debris. It can continuously exfoliate the stent surface, expose internal antibacterial agents, and remove adherent bacteria and proteins. The stent exhibited a remarkable antibiofilm property and reduced the level of inflammatory and necrotic cells after three weeks of implantation. (2) The antibacterial agents were firmly attached to the degrading matrix by hydrogen bonding, thereby resulting in long-term bactericidal activity, low total release of the antibacterial agent (6.7%, 8 μg), and low cytotoxicity (with a relative growth rate of >80% of L929 cells). Graphical abstract: Image, graphical abstract